Upaya Meningkatkan Kreativitas Dan Hasil Belajarsiswa Pada Pokok Bahasan Perbandingan Dan Skala Berbantu Media Visual Dan Benda Konkrit (PTK Pada Siswa Kelas VII A SMP Negeri 1 Tanon Tahun 2014/2015) - Anitasari, Jihan Fauzin; , Prof. Dr. Budi Murtiyasa, M.Kom (2015)
This research is conducted to improvement the creativity and learning outcomes of the students on the subject of comparison and scale with learning that using the visual media and concrete objects in class VII-A SMP Negeri 1 Tanon. This type of research is a classroom action research (CAR) conducted collaboration between teachers of mathematics with researchers. Students class VII-A as the subject of the action recipients are 32 students, teachers as subjects giver action, and principals as auxiliary subjects in the planning and research data collection. The method of collecting data was conducted by observation, notes field sheet and documentation. The technical of analyzing data consists of: data reduction, data presentation, and conclusion drawing. The research results shows the improvement creativity and mathematical learning outcomes of students. It can be seen from the students' ability to 1) answered questions from teachers and other students before the treatment 12,50% became 34,37%, 2) work on the problems in front of the class before the treatment 6,25% became 28,12%, 3) completing math problems by using more than one way before the treatment 18,75% became 40,62%, 4) ask questions before the treatment 9,37% became 31,25%. Mastery level students who scored more than equal to 75 before the treatment 53,12% became 93,75%. Based on the above set out above it can be concluded that the application of learning that using visual media and concrete objects can improvement creativity and mathematical learning outcomes of students on the subject of comparison and scale.